Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3389/fpsyt.2023.1098610
|View full text |Cite
|
Sign up to set email alerts
|

Attention bias modification for depression: A systematic review and meta-analysis

Abstract: BackgroundDepression is a mental health disorder characterized by affective, somatic, and cognitive symptoms. Attention bias modification (ABM) has been widely used to treat depression. However, the results seem inconsistent. We conducted a systematic review and meta-analysis to investigate the efficacy of ABM for depression and to explore the optimal protocol of ABM.MethodsSeven databases were systematically searched from their inceptions to 5 October 2022 to include randomized controlled trials (RCTs) of ABM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…This is in line with the theoretical promise of using EEG-based neurofeedback to modify affect-biased attention, as EEG offers the marriage of precise neural measures and feasible clinical translation (Woody and Price, 2022 ). In addition, the current findings suggest that our BCI overcomes some of the reliability and interpretability challenges associated with previous ABMTs (Price et al, 2015 ; Rodebaugh et al, 2016 ; Xia et al, 2023 ). Finally, our use of AR technology is a novel application that could be used to enhance participant comfort and engagement.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…This is in line with the theoretical promise of using EEG-based neurofeedback to modify affect-biased attention, as EEG offers the marriage of precise neural measures and feasible clinical translation (Woody and Price, 2022 ). In addition, the current findings suggest that our BCI overcomes some of the reliability and interpretability challenges associated with previous ABMTs (Price et al, 2015 ; Rodebaugh et al, 2016 ; Xia et al, 2023 ). Finally, our use of AR technology is a novel application that could be used to enhance participant comfort and engagement.…”
Section: Discussionmentioning
confidence: 56%
“…Initial interest in modifying affect-biased attention to improve depressed mood stemmed from observations that antidepressants, such as selective serotonin reuptake inhibitors (SSRIs), led to reductions in attention to negative information, preceding improvements in mood (Browning et al, 2010 ). Attention bias modification training (ABMT) has since been tested as a possible treatment for depression, and a recent meta-analysis from adult samples revealed that ABMT leads to significant reductions in depressive symptoms (Xia et al, 2023 ). However, this review and others (Price et al, 2015 ; Rodebaugh et al, 2016 ) have also shown that existing ABMT paradigms are limited by reliability and interpretability challenges, and there is a need to enhance the robustness and precision of these interventions.…”
Section: Introductionmentioning
confidence: 99%
“…This suggested better stress coping skills following Amyg-EFP-NF relative to controls. Wald et al 50 conducted attention bias modification training (ABMT) which is an intervention method, where a pre-designed processing mode is used to directly manipulate attentional bias through task scenarios, 60 and they reported four sessions of ABMT reduced risk for PTSD associated with the no-training condition. In addition, no other between-group differences were found.…”
Section: Methodsmentioning
confidence: 99%
“…As in previous studies in the field [76][77][78][79], the risk of bias will be assessed using the second version of the Cochrane RoB tool (RoB2) [80] for randomized trials, classifying them as low, some concerns or high risk according to the analysis of five domains: randomization process, deviations from intended interventions, missing outcome data, measurement of the outcome, and selection of the reported result. The risk of bias will be evaluated by two authors (F.C.-O.…”
Section: Risk Of Bias Of Individual Studiesmentioning
confidence: 99%